PEMANTAUAN VITAL SIGNS UNTUK PASIEN COVID-19 DENGAN MENGINTEGRASIKAN IOT DEVICE DENGAN STANDAR DATA KESEHATAN - Budi Santoso, Misbah (CV. Hawari, 2022)
Direct visits to patients who are confirmed positive for COVID-19 are very risky and medical personnel are among those who have a risk of being exposed to COVID-19. Use of technology to reduce the risk of medical personnel being exposed is very necessary,use of sensors for remote monitoring of vital signs that can reduce the workload and risk of exposure and reduce manual recording errors.The research objective is to design and build an IoT based vital signs monitoring tool and build a prototype that supports the security and accuracy of data exchange.IoT for vital signs monitoring tool will be integrated with the hospital information system using middleware.uses the Engineering Design Process method which has been proven to be frequently used in the design process.processes carried out are data requests and data transmission,data transformation and data presentation, using middleware as the recipient of requests and sending HL7, in the process of requesting and receiving that has been transformed according to health data standards. IoT for vital signs monitoring tools can be used as a means to protect medical workers from the risk of being exposed to COVID-19 and digital integration can facilitate the flow of information better and with minimal errors as well as the use of HL7.and has a more structured data form and can define the data structure of the information sent between systems,the Interoperability can reduce the need to perform manual data input which results in saving time and avoiding the problem of difficulty/errors in reading one's handwriting.